The Effectiviness of Ketapang (Terminalia cattapa L.) Leave Extract for the Treatment of Aeromonas salmonicida Infection in Catfish (Pangasioniodon hypophthalmus) - Sumino .; Asep Supriyadi; Wardiyanto . (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2013)
Abstract Catfish is one of the fish species with certain advantages that attract the farmers interest to culture. The species becomes popular following the successful spawning in the pond. Additionally, catfishes have high economic value due to their rapid growth and response to good artificial feed. Their farming activities are inseparable from concerns about their potential diseases. Diseases in farmed fish can be caused by fungi, parasites, bacteria and viruses. One type of bacterium to take serious control is Aeromonas salmonicida. This pathogenic bacteria may cause furuncle and death of farmed fish. The use of ketapang leaves is effective in inhibiting or killing the pathogenic A. salmonicida in catfish. In the present study, each test used a sample of 10 catfishes of approximately 10 cm in size. Parameters of the test consist of survival rates and pathologic lesions. The feed treatment consisted of ketapang leaf extract in concentrations of 100, 200, and 300 mg / ml, and a positive control and a negative control. Each treatment consisted of 3 replicates, and were analyzed statistically. The results indicated that the LD50 (Lethal Dose), MIC (Minimum Inhibitory Concentration) and MBC (Minimum Bactericidal Concentration) are 107 cfu/ml, 50 mg/ml and 100 mg/ml, respectively. The most effective concentration of ketapang leaf for the treatment of A. salmonicida infection in the catfish is 200 mg/ml. This is indicated by the highest level of catfish survival and the lowest rate of the pathologic lesions.